Licensure examination performance and academic achievement of teacher education graduates - Jay-cen Tamayo Amanonce; Ariel Macarubbo Maramag (International Journal of Evaluation and Research in Education (IJERE), 2020)
Teacher education institutions (TEIs) in the Philippines establish their brand of educational quality through their graduates’ performance in the Licensure Examination for Teachers (LET). It is, therefore, necessary for TEIs to align instructional delivery with the competencies in the LET. Thus, this study was undertaken to correlate academic achievement and licensure examination performance of teacher education graduates. Academic achievement is the graduates’ grade weighted average in college and pre-board examination results. The respondents were 1,017 graduates of Bachelor of Secondary Education and Bachelor of Elementary Education in a state university in Cagayan Province, Philippines. The study revealed a significant and strong correlation between the graduates’ grade weighted average in college and LET performance. This is an indication of the effective evaluation procedure of the university since the teachers’ assessment concurs with the graduates’ performance in the LET. A significant relationship was also established between the graduates’ performance in the pre board examination and LET albeit with a weak correlation. This study recommends the development of mechanisms in improving the conduct of pre-board examination review programs in the university. Further validation of the assessment tools used in the pre-board examination is likewise suggested.